Estrategias metodológicas para el aprendizaje en el área multimedia en los estudiantes de tercero de bachillerato de la Unidad Educativa Puebloviejo - Muñoz Murillo, Henry Alberto (2019)
The following case study is found in several chapters where the problems we observe and analyze the methodological strategies used by teachers of the third baccalaureate of the Puebloviejo Unit are found, in the same way what type of study was carried out to obtain of the information that they will contribute to the conclusion and recommendation before this type of problematic problems, and thus will determine the possible solution to the observed problems, in this way the teachers will apply the methodological strategies in a more correct way in the classrooms with the students to obtain meaningful learning, and so they will use multimedia tools to difficult the teaching-learning process.